Evaluation of Biventricular Functions With Tissue Doppler Imaging in Patients With Myotonic Dystrophy - ÖZBEN SADIÇ, BESTE (WILEY, 2010)
Background: Myotonic dystrophy (MD) is characterized by myotonia with dystrophic involvement of the muscles. Cardiac involvement is usually not evident in the early stages of MD. Hypothesis: We investigated biventricular functions by tissue Doppler imaging (TDI) in MD patients with no overt cardiac involvement to explore the value of TDI in the early detection of myocardial dysfunction. Methods: A total of 21 MD patients (15 male, age: 32.2 +/- 12.3 yrs) and 21 healthy controls (13 male, age: 32.2 +/- 7.8 yrs) were included. In addition to conventional echocardiography, pulsed Doppler and TDI were performed including measurement of myocardial performance index (MPI); peak systolic (Sm) and early (Em) and atrial (Am) diastolic myocardial velocities at the basal mitral and tricuspid annulus. Results: All patients and controls had normal ejection fraction. Transmitral E peak velocity was significantly lower while both deceleration time of E velocity and isovolumic relaxation time were significantly longer in MD patients (P = 0.007, P = 0.001, and P < 0.001, respectively). Sm, Em and Am peak velocities were significantly lower in MD patients in all segments except for Em of the mitral anterior annulus and Am of the tricuspid lateral annulus. Both left and right ventricular MPI were significantly higher in MD patients (P < 0.001. and P = 0.013, respectively). Conclusion: There are changes in myocardial systolic and diastolic functions in MD patients although they have no overt heart failure. Myocardial tissue velocities and MPI are useful in identifying subclinical biventricular involvement in these patients.
Keywords: VENTRICULAR DIASTOLIC FUNCTION; CARDIAC INVOLVEMENT; MYOCARDIAL PERFORMANCE; CONDUCTION SYSTEM; CTG REPEAT; VELOCITY; INDEX